Digital Communication Ethics from a Sufi Perspective: The Takhalli-Tahalli-Tajalli Model Against Information Disorder - Saifulloh, Moh; Samsuriyanto, Samsuriyanto (INJECT (Interdisciplinary Journal of Communication), 2026)
This research aims to formulate a digital communication ethics framework by transposing the classical Sufi model of Takhalli (cleansing), Tahalli (beautifying), and Tajalli (manifestation) from Imam Al-Ghazali and Imam Al-Jailani. In the contemporary cyber era, conventional legal-structural and techno-centric paradigms function merely as reactive, external controls that fail to address the psychological motives behind information disorder. This study benefits digital society by shifting the mitigation paradigm from reactive containment to internal, preventive self-regulation. Methodologically, this study adopts an interpretivist paradigm using a qualitative critical literature review integrated with Gadamerian Philosophical Hermeneutics. The results demonstrate that the framework operates as a closed-loop cybernetic system. Specifically, Takhalli purges kizb, hasad, and riya’. This qualifies Tahalli to implement two-tiered behavioral interventions via Sidq and Rahmah. Ultimately produces Tajalli—manifesting as “Digital Ihsan” anchored by Digital Muraqabah. Although platform anonymity poses structural limitations at the cyber-deindividuation threshold, this model permanently breaks the supply chain of toxic information.